Trends in Piezo Channel Research Over the Past Decade: A Bibliometric Analysis - Guo, Jing; Gu, Dongmei; Zhao, Tingting; Zhao, Zhanhao; Xiong, Yajun; Sun, Mengzhu; Xin, Chen; Zhang, Yujie; Pei, Lixia; Sun, Jianhua (Frontiers in Pharmacology, 2021)
Purpose: We used bibliometric methods to evaluate the global scientific output of research on Piezo channels and explore the current status and trends in this field over the past decade. Methods: Piezo channel-related studies published in 2010–2020 were retrieved from Web of Science. The R bibliometrix package was used for quantitative and qualitative analyses of publication outputs and author contributions. VOSviewer was used to construct networks based on co-authorship of countries/institutions/authors, co-citation analysis of journals/references, citation analysis of documents, and co-occurrence of keywords. Results: In total, 556 related articles and reviews were included in the final analysis. The number of publications has increased substantially with time. The country and institution contributing the most to this field was the United States and Scripps Research Institute, respectively. Ardem Patapoutian was the most productive author and ranked first among the cited authors, h-index, and m-index. The top cited reference was the article published by Coste B et al. in Science (2010) that identified Piezo1/2 in mammalian cells. The top journals in terms of the number of selected articles and citations were Nature Communications and Nature, respectively. The co-occurrence analysis revealed that Piezo channels are involved a variety of cell types (Merkel cells, neurons, endothelial cells, red blood cells), physiological processes (touch sensation, blood pressure, proprioception, vascular development), related ion channels (transient receptor potential, Gardos), and diseases (pain, distal arthrogryposis, dehydrated hereditary stomatocytosis, cancer), and pharmacology (Yoda1, GsMTx-4). Conclusion: Our bibliometric analysis shows that Piezo channel research continues to be a hotspot. The focus has evolved from Piezo identification to architecture, activation mechanism, roles in diseases, and pharmacology.